Asymmetric synthesis of a cyclopropanecarboxylic acid derivative – the potential agonist/antagonist of GABA receptors. (22nd June 2022) - Rzewnicka, Aneta; Krysiak, Jerzy; Mikina, Maciej; Żurawiński, Remigiusz; Sobczak, Agata; Sieroń, Lesław
Abstract: The synthesis of enantiomerically pure (1 S, 2 S, S P )-1-[hydroxy(methyl)phosphonyl]-2-aminocyclopropanecarboxylic acid (1 ) (a potential agonist/antagonist of GABA receptors) was accomplished in six steps based on optically inactive methyl 2-[methoxy(methyl)phosphonyl]acrylate (2 ). The key steps of this synthesis included the cyclopropane ring formation by the asymmetric cyclopropanation reaction of 2 with ( S )-dimethylsulfonium( p -tolylsulfinyl)methylide (3 ), regio and stereoselective installation of ethoxycarbonyl group in the cyclopropane ring, and the chemoselective desulfinylation reaction conducted with phenylsilane under the basic conditions. Graphical Abstract: UF0001